PERANCANGAN DAN SIMULASI DESAIN KONSEPTUAL ALAT TRANSPORTASI PASCA PANEN PEDESAAN (Conceptual Design and Simulation of Rural Post-harvest Transportation) - M. Vahringga Mandatya; Taufik Rizaldi (Universitas Sumatera Utara, 2019)
Transportation is a very important means to support the economy in rural area. Therefore, it’s necessaryto design rural post-harvest transportation that can be operated easily and simulate the design to find out the strength of the tool design. The parameters observed in the conceptual model simulation test are the stress, deformity and FoS of the tool’s axle shafts and frame to determine it’s capability to sustain the tool’s load. The result of the static stress simulation also showed that the greatest stress value the container tub had to endure from the load was 26,89 N/mm2, with maximum deformity of 0.85 mm and 21,89 being the smallest FoS value.The greatest stress value the upper frame had to endure from the load was 38,514 N/mm2, with maximum deformity of 0.176 mm and 15,3 being the smallest FoS value. While the greatest stress value the bottom frame had to endure from the load was 8,726 N/mm2, with maximum deformity of 0.087 mm and 67,66 being the smallest FoS value. The greatest stress value the front axle shaft had to endure from the load was 7,74 N/mm2, with maximum deformity of 0.008 mm and 32,38 being the smallest FoS value. While, the greatest stress value the rear axle shaft had to endure from the load was 61,65 N/mm2, with maximum deformity of 0.29 mm and 4,05 being the smallest FoS value. Keywords: Design, Transportation, Simulation. ABSTRAK Transportasi merupakan sarana yang sangat penting untuk mendukung perekonomian masyarakat tak terkecuali di daerah pedesaan. Oleh karena itu, perlu dilakukan perancangan alat transportasi pasca panen pedesaan yang dapat dioperasikan dengan mudah dan simulasi desain alat untuk menguji kekuatan rancangan alat tersebut. Parameter yang diperhatikan saat pengujian simulasi model konseptual alat adalah tegangan, tingkat deformasi serta FoS yang terjadi pada model konseptual bak penampung, poros roda dan rangka alat untuk mengetahui ketahanannya dalam menahan beban alat. Dari hasil simulasi statis model konseptual alat, bak penampung mengalami tegangan dari pembebanan sebesar 26,89 N/mm2, dengan deformasi maksimum sebesar 0,85 mm dan nilai FoS terkecil sebesar 21,9. Rangka alat bagian atas mengalami tegangan dari pembebanan sebesar 38,514 N/mm2, dengan deformasi maksimum sebesar 0,176 mm dan nilai FoS terkecil sebesar 15,3. Sedangkan rangka alat bagian bawah mengalami tegangan dari pembebanan sebesar 8,726 N/mm2, dengan deformasi maksimum sebesar 0,087 mm dan nilai FoS terkecil sebesar 67,66. Poros roda depan mengalami tegangan dari pembebanan sebesar 7,74 N/mm2, dengan deformasi maksimum sebesar 0,008 mm dan nilai FoS terkecil sebesar 32,28. Sedangkan poros roda belakang mengalami tegangan dari pembebanan sebesar 61,65 N/mm2, dengan deformasi maksimum sebesar 0,29 mm dan nilai FoS terkecil sebesar 4,05. Kata kunci: Desain, Transportasi, Simulasi